University Students’ and Lecturers’ Needs in General English Subject at PGRI Silampari University - Yulfi, Yulfi; Rizki, Rahmatika Sri Dewi; Oktaviani, Ayu (EDULIA: English Education, Linguistic and Art Journal, 2023)
This research aimed to find out the University Students’ Needs in Learning General English Subject at PGRI Silampari University and the lecturer needs in designing RPS. The method in this research was descriptive qualitative. The population of this research was non English education study program students especially history education study program consist of 130 students. The sample of this research was sixth semester students with 28 students that was choosen by using purposive sampling. The data were collected by using questionnaire and interview. After that, the data were analyzed with description. The results showed that the purpose most of students learn English is being able to communicate with English and can speak English fluently. The students’ want from the lecturer were to help them to mastering English skills, make an enjoyable class, and give them interesting teaching method. Students’ wants of using English skills were they can being able to communicate with English, they can understand what the lecturer said in English, and can help them in applying job in the future. Furthemore, the students’ lacks were in speaking English, lack in writing, lack in listening and less of confidence with their skills. As the conclusion, the students’ needs more spesific English material that related to their major and interesting learning method from the lecturer to fulfil their needs. The lecturers’ need in designing syllabus were the lecturer should know the used of curiculum and what do the students usually learn. From those aspect the lecturer looking for the references that can be used to design materials to be given in one semester, which are on the syllabus add English components and English skills that related to their need and major. And also the material is more adapted to topics related to history education study program. Keywords: General English Subject, Lecturers, Need Analysis, Students